Organizational Learning in the Hotel Industry: an eclectic instrument of measurement - Fernandes, A. L.; Laureano, R. M. S.; Alturas, B. (Tourism and Management Studies, 2018)
Organizational Learning, despite being a widely debated topic in the literature on management, regarding the hotel industry still suffers from scattered information. This study was conducted with 295 professionals, among them managers and employees of hotels in Brazil and Portugal in order to validate a measuring instrument of organizational learning, properly adapted for hotel industry, and identify differences in the degree of efficiency of the organizational learning process between hotels of different categories, and between managers and employees. Initially a content validation with representatives of the hotel industry was made, than a confirmatory factor analysis was performed. As a result, we obtained a scale with 4 factors and 12 items, which was able to identify differences in the level of organizational learning between hotels and between managers and employees. There is evidence that the ability of individuals and groups to learn is encouraged, but is not being achieved in full in this industry, and that the most critical part of the process involves the dimension of creation and knowledge management in this industry.